Phytoremediation of municipal wastewater using aquatic macrophytes / Caroline Marajan ... [et al.] - Marajan, Caroline; Johnny, Diane Joanne; Peter Diman, Caroline; Hambali, Satira; Abdul Wahab, Kamsiah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Under present investigation, the efficiency of two different aquatic macrophytes was tested for the treatment of municipal wastewater collected from the sewage treatment plant (STP), Universiti Teknologi MARA (UiTM) Pulau Pinang. The experiments were operated by placing the raw wastewater into six similar storage containers having dimensions of 0.37 m (L) x 0.29 m (W) x 0.3 m (D). The containers were then divided into three groups, where each group has its duplicates. Four containers were placed with the locally available aquatic macrophytes for the treatment of wastewater; two containers with Centella asiatica and the other two containers with Eichhornia crassipes. The last two containers acted as the control sample. Initial concentrations of the raw wastewater parameters were determined. To evaluate the treatment efficiency of each macrophyte, pH, temperature, BOD5, COD and NH3-N of the wastewater taken from the outlet (effluent) of the containers were tested for the duration of 10 days. The average reduction of effluent value of each parameter using Centella asiatica were 52.0% for BOD5, 46.4% for COD and 73.0% for NH3-N. For Eichhornia crassipes, the average reduction efficiency for selected parameters were 55.0% for BOD5, 35.9% for COD and 58.8% for NH3-N. There were no significant changes on the pH values and the temperature remained unchanged throughout the experiment. All parameters tested were within the permissible standard allowed based on Standard B taken from the Environmental Quality Act (EQA), 1974. Phytoremediation model was used to predict the treatment potential of the existing municipal wastewater using the aquatic macrophytes. It was observed that the model was appropriate to describe the phytoremediation potential of the aquatic macrophytes. It was suggested that by extending the duration of treatment, the model can be applied for this study. The current study indicated that Centella asiatica and Eichhornia crassipes can be utilized for the phytoremediation of municipal wastewater